An Analysis of Linguistic Politeness in the Comment Sections of TikTok Social Media - Aulia Putri; Murmi Anjani; Siska Ananda; Juli Yani; Asri Yulianda (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study aims to analyze linguistic politeness in the comment sections of the social media platform TikTok. TikTok, as one of the most popular social media platforms today, serves as a space for users to express themselves and interact directly through the comment feature on creators' video content. However, the anonymity and freedom within these comment sections often lead to various forms of language use, including those that violate politeness principles. This research seeks to explore how TikTok users either adhere to or violate the principles of linguistic politeness in their comments. The findings reveal that while polite language and respect for others' opinions are still widely observed, numerous comments exhibit violations of politeness, such as the use of harsh words, derogatory remarks, insults, and sarcasm. Although politeness in language can still be found, the greatest challenge in maintaining ethical communication on social media lies in the high level of anonymity, which often triggers impolite and disrespectful language behavior. This study underscores the importance of digital literacy to raise awareness about the significance of politeness in communication.